2015
DOI: 10.4149/neo_2015_033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of ERG rearrangement subtype and its association with increased p53 expression in Japanese and German prostate cancer

Abstract: ERG, p53, prostate cancer, TMPRSS2-ERG fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In the analysis of reviewed articles, there was a consistency between the relationship of ERG protein expression and the biochemical recurrence of PCa ( 38 , 40 , 57 , 61 63 ). Hagen et al showed that 13 of 28 patients (46.4%) who had surgical specimens with high ERG levels developed recurrence compared to only 3 (12%) of 25 patients who had tumors with low ERG levels ( p = 0.006) ( 57 ).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In the analysis of reviewed articles, there was a consistency between the relationship of ERG protein expression and the biochemical recurrence of PCa ( 38 , 40 , 57 , 61 63 ). Hagen et al showed that 13 of 28 patients (46.4%) who had surgical specimens with high ERG levels developed recurrence compared to only 3 (12%) of 25 patients who had tumors with low ERG levels ( p = 0.006) ( 57 ).…”
Section: Resultsmentioning
confidence: 87%
“…Of the selected articles, the analyzed materials in the studies were specimens from prostatectomies (17 studies) ( 25 , 33 , 38 , 40 45 , 55 59 , 61 63 ), TUR (3 studies) ( 33 , 38 , 59 ), biopsies (2 studies) ( 38 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Whether TMPRSS2 is involved in various tumors’ pathogenesis via certain molecular mechanisms remains to be elucidated. TMPRSS2 has been found to inhibit colorectal cancer cell migration ( Bowden et al, 2007 ), and its expression was diminished in cases with P53 mutations ( Nishijima et al, 2015 ). In addition, TMPRSS2 was also taken a key part in HCC by driving the recruitment and differentiation of peritumoral fibroblasts into TAMs ( Thunders and Delahunt, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer PC-3 is a kind of hormone-independent cancer cell [ 20 22 ]. This study used a BALB/c nude mouse model inoculated with human PC-3 cells to simulate prostate cancer growth in vivo .…”
Section: Discussionmentioning
confidence: 99%